Oportunidades y riesgos para la cooperación universitaria para el desarrollo en el espacio europeo de educación superior - Gómez-Torres, Mª de los Llanos; Calabuig Tormo, Carola; Boni Aristizábal, Alejandra; Peris Blanes, Jordi; Monzó Balbuena, José (Revista Española de Desarrollo y Cooperación, 2023)
The European Higher Education Area (EHEA) is an ambitious and complex plan, promoted by European Countries, which focuses on the European convergence in the field of universitary education. This paper focuses on the opportunities and risks that the EHEA presents for universitary development cooperation instruments, with a special emphasis in those related with training. The university model that we present in this paper is an institution that forms excellent professionals but also people and citizens committed with the goal of human and sustainable development.